Microbial biodiversity profiling of spontaneous fermentation of Garcinia Mangostana pericarps / Azreen Zainaldin - Zainaldin, Azreen (2018)
The spontaneous fermentation of Garcinia Mangostana pericarps was carried out over 90 days of period in order to enumerate the population dynamic of fermented mangosteen pericarps. The fermentation was conducted anaerobically in 50L benchtop bioreactor. Then, the samples was collected on each sampling day at day 5, 10, 20, 30, 45, 60, 75 and 90. The collected samples were cultivated on four different type of media which are Mac Conkey (MC), Man Ragosa Agar (MRS), Plate Counting Agar (PCA) and Potato Dextrose Agar (PDA) in order to determine the presence of Enterobacteriaceae, Lactic Acid Bacteria, Total Bacteria and Yeast respectively. DNA of bacteria and yeast were extracted and followed by PCR amplification using universal primer set. The sequencing of 16S rDNA gene of bacterial isolates yielded 5 genera and 7 species which are Enterococcus (1 species), Bacillus (1 species, Gluconobacter (1 species), Enterobacter (2 species) and Azotobacter (1 species) while the sequencing result of 5.8S-ITS rDNA gene of random selected isolates on PDA media from all sampling days yielded only 2 genera with 5 species including Hanseniaspora (4 species) and Candida (1 species). An Enterococcus faecalis which is one of the common species of Lactic Acid Bacteria (LAB) was become major bacterial group that presence in random selected isolates. The LAB has an ability to improve the nutritional value of food by providing and acidic condition in fermented food. In this acidic condition shows that the pathogens could not survive started from day 10 until the end of fermentation. However, in this study the small amount of LAB population was identified due to the limited number of random selected isolates.